2004
DOI: 10.4049/jimmunol.173.7.4643
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Dependent Requirement for Granulocyte-Macrophage Colony-Stimulating Factor in Inflammation

Abstract: Data from several inflammation/autoimmunity models indicate that GM-CSF can be a key inflammatory mediator. Convenient models in readily accessible tissues are needed to enable the GM-CSF-dependent cellular responses to be elaborated. In this study, we show that, in contrast to the response to the commonly used i.p. irritant, thioglycolate medium, an Ag-specific methylated BSA-induced peritonitis in GM-CSF−/− mice was severely compromised. The reduced response in the latter peritonitis model was characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 47 publications
8
77
1
Order By: Relevance
“…Similar results were obtained using GM-CSF Ϫ/Ϫ mice or C57BL/6 mice treated with anti-GM-CSF mAb. This finding of a normal early, predominantly neutrophil, response but a later defective macrophage response in K/BxN serum-transfer arthritis induced in GM-CSF Ϫ/Ϫ mice is similar to what we observed in the methylated bovine serum albumin-induced peritonitis model in these mice (22). It has been suggested that macrophages are most likely important after the initiation of K/BxN serum-transfer arthritis, being a major source of proinflammatory cytokines (45), whereas neutrophils are required in the early stage involving the vascular permeability that precedes disease onset (46).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were obtained using GM-CSF Ϫ/Ϫ mice or C57BL/6 mice treated with anti-GM-CSF mAb. This finding of a normal early, predominantly neutrophil, response but a later defective macrophage response in K/BxN serum-transfer arthritis induced in GM-CSF Ϫ/Ϫ mice is similar to what we observed in the methylated bovine serum albumin-induced peritonitis model in these mice (22). It has been suggested that macrophages are most likely important after the initiation of K/BxN serum-transfer arthritis, being a major source of proinflammatory cytokines (45), whereas neutrophils are required in the early stage involving the vascular permeability that precedes disease onset (46).…”
Section: Discussionsupporting
confidence: 89%
“…As to GM-CSF dependence of a particular pathology, we have found that the requirement for GM-CSF in inflammatory responses is stimulus dependent, with methylated bovine serum albumin-induced peritonitis being GM-CSF dependent, while thioglycollate-elicited peritonitis is GM-CSF independent, in relation to cell numbers (22).…”
mentioning
confidence: 98%
“…This raises the possibility that the reduced eosinophilic inflammation in the GM-CSF Ϫ/Ϫ mice may be caused by the pulmonary abnormalities of these animals, rather than by a defect in allergic inflammatory reactions. However, a study on inflammation in another site, the peritoneal cavity, reported fewer eosinophils in the peritoneal lavage of GM-CSF Ϫ/Ϫ mice compared with that of WT animals (40). These findings indicate that defects in tissue eosinophilia are not limited to the lung, but are a general feature of GM-CSF Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 72%
“…Acute peritonitis was induced as described previously (3,22). On days 0 and 14, mice were injected intradermally at the base of the tail with 100 ml mBSA (1 mg/ml in CFA).…”
Section: Induction Of Acute Peritonitismentioning
confidence: 99%